Reichsparteitag Nürnberg Postkarte Ansichtskarte 1937 Photo-Hoffmann... - Uncredited illustrator (Wikimedia Commons, 1936)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg Postkarte Ansichtskarte 1937 Photo-Hoffmann München 36-7 Hitlerjugend HJ NSDAP Propaganda Reichsadler Burg Nazi Party Nuremberg Rally Postcard Uncredited artist (No signature) No known copyright restrictions. " Nuremberg Rally " (Reichsparteitag Nürnberg). Postcard painting of a uniformed member of the Hitler Youth (HJ) with Swastika flag (HJ flag), also Coat of arms of Nuremberg, Nazi style Reichsadler, and Nuremberg Castle in the background | Published by Photo-Hoffmann, Munich, Nazi Germany in 1936 (No. 36/7) | Nazi Party (NSDAP) propaganda | No signature (uncredited artist) and No known copyright restrictions.
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château